2003
DOI: 10.1093/emboj/cdg119
|View full text |Cite
|
Sign up to set email alerts
|

Pathway utilization in response to a site-specific DNA double-strand break in fission yeast

Abstract: We have examined the genetic requirements for efficient repair of a site-specific DNA double-strand break (DSB) in Schizosaccharomyces pombe. Tech nology was developed in which a unique DSB could be generated in a non-essential minichromosome, Ch(16), using the Saccharomyces cerevisiae HO-endonuclease and its target site, MATa. DSB repair in this context was predominantly through interchromosomal gene conversion. We found that the homologous recombination (HR) genes rhp51(+), rad22A(+), rad32(+) and the nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(98 citation statements)
references
References 49 publications
6
89
0
2
Order By: Relevance
“…Quantitative analysis of break repair in rad3D revealed a defect in HR repair, resulting in a significantly reduced level of GC (26%, P = 0.001) and a concomitant increase in Ch 16 loss (42%, P = 0.03) and LOH (27%, P = 0.0003) compared with wild type ( Fig. 6C; Prudden et al 2003), reminiscent of the repair profile observed in ddb1D and cdt2D. Furthermore, analysis of break repair following deletion of spd1 + in a rad3D background partially restored GC levels (37%, P = 0.05) and reduced levels of minichromosome loss (38%, P = 0.5) and LOH (20%, P = 0.01) compared with rad3D (Fig.…”
Section: Rad3 Facilitates Efficient Hr By Regulating Cdt2 and Dntp Lementioning
confidence: 98%
See 4 more Smart Citations
“…Quantitative analysis of break repair in rad3D revealed a defect in HR repair, resulting in a significantly reduced level of GC (26%, P = 0.001) and a concomitant increase in Ch 16 loss (42%, P = 0.03) and LOH (27%, P = 0.0003) compared with wild type ( Fig. 6C; Prudden et al 2003), reminiscent of the repair profile observed in ddb1D and cdt2D. Furthermore, analysis of break repair following deletion of spd1 + in a rad3D background partially restored GC levels (37%, P = 0.05) and reduced levels of minichromosome loss (38%, P = 0.5) and LOH (20%, P = 0.01) compared with rad3D (Fig.…”
Section: Rad3 Facilitates Efficient Hr By Regulating Cdt2 and Dntp Lementioning
confidence: 98%
“…2B; Tinline-Purvis et al 2009). Following break induction, wild-type cells predominantly repair the break by HR repair (61%), resulting in arg + hyg S ade + his + colonies in which the MATa break site and adjacent Hyg R marker are lost through gene conversion (GC) using the endogenous ChIII as a repair template (Prudden et al 2003). In contrast to wild type, significantly reduced levels of GC were observed in both ddb1D (34%, P = 0.005) and cdt2D (33%, P = 0.02) backgrounds following break induction, an outcome indicative of inefficient HR.…”
Section: Ddb1 and Cdt2 Are Required For Hrmentioning
confidence: 99%
See 3 more Smart Citations